CLEAN ENERGY A CDM PROJECT OPTION - ChÃ¡vez, Milka E. Escalera; Fonseca, Gustavo Gallegos; Vaca, Julio Cesar Leal (European Scientific Journal, ESJ, 2014)
Projects â€œAnimal Waste Management System Green House Gas Mitigation Project (AWMS GHG Mitigation Project)â€ are a practical alternative solution to the pollution problem from hog farms. The project offers to reduce the high emissions of greenhouse gases (GHG) by placing the manure in closed anaerobic digesters that produce biogas, which is then burned to prevent methane emissions. However, the biogas produced can be used to generate energy, which can be utilized for the activities in the farm. The study seeks, among other things, to analyze if the energy produced by methane allows hog farm owners to obtain profits after the consumption, demand and payment of electricity. The data used in this study were obtained from the UNFCCC registered CDM projects in 2005 which are valid until today. The project feasibility was determined from the Net Present Value, Internal Rate of Return (IRR) and Benefit/Cost ratio. The results permit to explain that the inclusion of CDM projects in agribusiness impulse regional development by making use of renewable energy produced from the excreta of pigs and that the agricultural sector can use it in their